Molecular signaling in spermatogenesis and male infertility - Singh, Rajender (Scientist) (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
Spermatogenesis involves the coordination of a number of signaling pathways, which culminate into production of sperm. Its failure results in male factor infertility, which can be due to hormonal, environmental, genetic or other unknown factors. This book includes chapters on most of the signaling pathways known to contribute to spermatogenesis. Latest research in germ cell signaling like the role of small RNAs in spermatogenesis is also discussed. This book aims to serve as a reference for both clinicians and researchers, explaining possible causes of infertility and exploring various treatment methods for management through the basic understanding of the role of molecular signaling. Key Features Discusses the signaling pathways that contribute to successfulspermatogenesis Covers comprehensive information about Spermatogenesis atone place Explores the vital aspects of male fertility and infertility Explains the epigenetic regulation of germ cell developmentand fertility Highlights the translational opportunities in molecular signalingin testis
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / General; MEDICAL / Family & General Practice; MEDICAL / Gynecology & Obstetrics; Cellular signal transduction; Spermatogenesis